The Concept of Building Revitalization with Office Functions as an Effort to Preserve Indies Buildings (Case Study: Bank Indonesia, Main Post Office, and BNI Bank in the Gondomanan Region, Yogyakarta) - Tony Kunto Wibisono; Vini Asfarilla; Nensi Golda Yuli (Departement of Architecture, Universitas Islam Indonesia, 2020)
The Gondomanan region is filled with increasingly active economic activity nowadays. As a result, changes cannot be avoided. This phenomenon results in old buildings such as indies buildings decreasing in quality and even being at risk of disappearing. Therefore preservation efforts in the form of revitalization activities must be carried out to keep the legacy from being destroyed. Developed countries in Europe and Britain have been carrying out conservation activities since World War I. The Indonesian government has also made conservation efforts as evidenced by the Law No. 11 of 2010 concerning Cultural Heritage. The purpose of this study is to analyze how the application of the concept of revitalization in indies buildings to still have office functions while also adjusting to the current conditions, so that they are considered successful in applying the concept of revitalization to provide economic, social, and cultural value. The method used is a qualitative method where data is obtained from literature studies and field observations then being analyzed to obtain information in the form of revitalization efforts that have been made. The results of this study show that the revitalization efforts in the case study are considered successful because the changes that occurred are not too significant and adjusted to the principles of the preservation of Burra Charter, seen from the aspects of spatial layout, facade, material, structure, and color. Keywords: Conservation-Preservation, Indies Architecture, Office Building, Revitalization